Dissemination of tumor cells in patients undergoing surgery for colorectal cancer - Weitz, Jürgen; Kienle, Peter; Lacroix, Jeannine; Willeke, Frank; Benner, Axel; Lehnert, Thomas; Herfarth, Christian; Knebel Doeberitz, Magnus von (Clinical cancer research, 1998)
The majority of patients with colorectal cancer present at a stage when the primary cancer can be resected with curative intent. However, despite the high resectability rate, about 30-50% of these patients subsequently develop metastatic disease. In these patients, neoplastic cells were disseminated either before or during surgery of the primary cancer. Due to the lack of appropriate detection systems, the extent of pre- and intraoperative hematogenic tumor cell dissemination has not yet been determined. Using a reverse transcription-PCR assay to amplify cytokeratin 20 transcripts, we were able to detect 10 colorectal cancer cells in 10 ml of blood. Blood samples were taken from 65 patients undergoing resection of primary colorectal cancer or liver metastasis of colorectal cancer pre-, intra-, and postoperatively. Circulating tumor cells were detected in 24 of 58 patients with colorectal resections in correlation to the tumor stage and in 6 of 7 patients who underwent hemihepatectomy for liver metastasis. In 8 of 58 patients with colorectal resection and in 5 of 7 patients with hemihepatectomy, tumor cells could only be detected during or during and after surgery. These results demonstrate that hematogenic tumor cell dissemination is a frequent and early event in colorectal cancer. Surgery enhances the release of tumor cells into the circulation. The long-term follow-up of our patient cohort will provide data on the prognostic relevance of circulating tumor cells and might lead to new therapeutic concepts for perioperative prophylaxis of tumor cell implantation or postoperative adjuvant therapy regimens.